The Improvement of Aircraft Carbon Dioxide Emissions Through The Use of Enhanced Gas is Carried Out According to The Requirements of The Standard - Prayitno, Hadi; Ekohariadi, Ekohariadi; Cholik, Mochamad; Suhartini, Ratna; Bahrawi, Ahmad; Wicaksono, Putra (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The current study aims to see that optimizing CO? emissions on aircraft through effective exhaust gas management is essential to achieving environmental sustainability in aviation. Sequentially, the literature review has enabled the study to identify current standards and regulations for aircraft CO? emissions, technologies for reducing aircraft CO? emissions, challenges in meeting CO? emission standards, environmental and economic benefits of optimized emission strategies and future research opportunities in aircraft emission reduction. This study uses literature data related to carbon dioxide emissions from aircraft. The findings are key strategies include optimizing fuel consumption, increasing sustainable aviation fuel (saf) production, and adopting novel technologies like turbine propulsion. Immediate actions and effective policies are essential for decarbonization, as the sector’s emissions continue to rise. future efforts should focus on electric propulsion and sustainable biofuels to mitigate climate change impacts. Immediate actions are important if carbon neutrality by 2020 and net-zero emissions by 2050 are to be possible; so this needs effective policies and increased funding for research. It is for this reason that the aviation sector should be among those going through urgent decarbonization processes due to the huge contribution it makes to CO? global emissions